ANALISIS KEUNGGULAN KOMPARATIF DAN KOMPETITIF KOMODITI BIJI PALA DI MINAHASA UTARA - Lidya Mega Gerungan; Caroline B.D. Pakasi; Joachim N.K. Dumais; Lorraine W. Th. Sondak, (COCOS, 2013)
ABSTRACT The Objective of this Research is to Analyzed Comparative and Competitive Advantages of Nutmeg Commodity in North Minahasa. The Research had been done for three-months, start from October 2012 until December 2012. Location of this research on Treman Village at Kauditan District – North Sulawesi. Data used in this research obtained from Primary and secondary data. Primary data was obtained from interviews with respondents by used a list of questions (questionnaires). While the secondary data was obtained from the relevant departments, such as Agricultural Department, Industrial Department, and Statistical Centre Department. The research result showed that is Nutmeg Farming in North Minahasa District has advantages using calculations of Private Profitability (19,777,223) and Social Profitability (46,919,419). It means that the Nutmeg Farming was efficient and had a competitive advantage and comparative advantage. Two indicators for measure competitiveness were 1) Private Cost Ratio (PCR) show result that Nutmeg Farmer’s is more competitive because PCR < 1; and 2) Domestic Resources Cost Ratio (DRCR) show result that Nutmeg Farming has comparative advantage because DRCR < 1. It means that the Nutmeg Farming according to financial analysis was efficient and has greater potency in perfect competition market.